Is biochar a reliable catalyst for activating peroxydisulfate? Damage of biochar during catalytic process. (September 2022) - Wan, Jiang; Wang, Gehui; Liang, Weiyu; Peng, Cheng; Zhang, Wei; Fu, Rongbing
Abstract: The unsatisfactory reuse performance of biochar in the catalytic system has become an important factor limiting its application. Damage of biochar in the catalytic systems has been reported, but the mechanism of damage is still unclear. In this study, cotton stalk and walnut shell biochar were used to activate peroxydisulfate (PDS) for sulfamethazine degradation, and multiple characterization methods were used to determine the damage of biochar. The comparative experiments of biochar, recycled biochar, and the biochar treated by PDS in catalytic reaction showed that the performance of biochars decreased by 37.5%–65.3%. After the catalytic reaction, the unstable carbon in biochar was lost, and the biochar surface was oxidized, which reduced its affinity to organic matter. CO2 physisorption showed that the pore structure of biochars barely changed. However, for walnut shell biochar, its adsorption capacity of nitrogen decreased obviously. Moreover, the electrochemical tests showed that the conductivity of walnut shell biochar decreased, which would lead to the reduction of its catalytic performance through the electron transfer path. Overall, the effects of catalytic process on the performance of biochar cannot be ignored. Therefore, more efforts are needed to improve the stability and homogeneity of biochar as an efficient and sustainable PDS activator. Graphical abstract: Image 1 Highlights: The catalytic efficiency of recycled biochar decreased significantly. The unstable carbon in biochar was lost, and the surface of biochar was oxidized. The catalytic process had no effect on the pore structure of biochar. The electrochemical properties of biochar decreased after catalytic reaction. Heterogeneity and instability of biochar hindered its use as a sustainable activator.